Integrasi Pendekatan STEAM dalam Perkuliahan Kalkulus Integral - Andi Trisnowali MS; Sartika Arifin (Pendidikan Matematika FKIP Universitas Mataram, 2023)
This research is a quantitative research that aims to improve student learning outcomes through the STEAM learning approach in Integral calculus courses. The populations in this study were all students taking the Integral Calculus course using a purposive sampling technique. The research design used was a quasi-experimental design with a nonequivalent control group design. Data were obtained from student learning outcomes tests in the form of pre-test and post-test. Data analysis used Mann-Whitney. The results showed that the sig (2-tailed) value for the experimental class was 0.000 <0.05, which means that the integration of the STEAM approach to Integral Calculus courses can improve student learning outcomes.